Kelayakan dan Praktikalitas Media Pembelajaran Menggunakan Aplikasi Sparkol Videoscribe terhadap Motivasi Belajar Siswa pada Mata Pelajaran Geografi di SMA N 4 Bukittinggi - Mai Liza Asmawati; Slamet Rianto; Loli Setriani (STKIP PGRI Sumatera Barat, 2022)
This study aims to determine and analyze the development, feasibility and practicality of Learning Media Development Using Sparkol Videoscribe on Students' Learning Motivation in Geography Subjects at SMA N 4 Bukittinggi.The type of research used in this research is research and development (Research and Development). The 4D model includes 4 stages, namely: Define, Design, Development, Desiminate. The subjects in this study were students of class XI IPS 1 and Class XI IPS 4 who took part in the geography learning process at SMA N 4 Bukittinggi in the academic year 2021/2022, with a total of 64 students.The results of the study found that: 1.) The development of the sparkol videoscribe learning media included validation from experts, namely media experts, education experts, and linguists. So that the media validation data is obtained and then processed with the Interaclass Coefitien Correlation (ICC) formula assisted by processing using the SPSS version 22 application for Windows, the result is 0.868. if the value is more than 0.5, it can be concluded that the level of validation is adequate. 2.) The sparkol videoscribe learning media was declared very feasible after analyzing data processing using Microsoft Excel so that the total score was 174 with a mean level of 4.37 and a percentage level of 87% with the predicate